Optimal incentive contracts for a worker who envies his boss - Robert Dur; Amihai Glazer (Center for Economic Studies and ifo Institute (CESifo), 2004)
A worker's utility may increase in his own income, but envy can make his utility decline with his employer's income. Such behavior may call for high-powered incentives, so that increased effort by the worker little increases the income of his employer. This paper uses a principalagent model to study optimal incentive contracts for envious workers under various assumptions about the object and generality of envy. Envy amplifies the effect of incentives on effort and, therefore, increases optimal incentive pay. Moreover, envy can make profitsharing optimal, even when the worker's effort is fully contractible. We discuss several applications of our theoretical work. For example, envy can explain why lower-level workers are awarded stock options, why incentive pay is usually lower in non-profit organizations, and higher in larger firms. Envy may also make governmental production of a good more efficient than private production.
Keywords: M52; J33; J31; 330; principal-agent; envy; moral hazard; compensation; incentives; contracts; profitsharing; stock options; public vs. private production; Anreizvertrag; Agency Theory; Moral Hazard; Neid